The influence of perceived social pressure, career aspiration, economic independence, and cultural values on attitude towards marriage among unmarried women in China - Ye, Chen; Ma’rof, Aini Azeqa; Abdullah, Haslinda; H. Hamsan, Hanina (Human Resource Management Academic Research Society, 2024)
This study explores the relationships between perceived social pressure, career aspiration, economic independence, and cultural values on attitude towards marriage among unmarried women in China. Using a quantitative approach, a sample of 458 participants completed validated measures, and Pearson correlation and multiple regression analyses were conducted to examine the relationships between the variables. The results revealed that perceived social pressure was the strongest predictor of positive attitude towards marriage, followed by cultural values, with both variables significantly shaping marriage attitudes. Conversely, career aspiration and economic independence were negatively correlated with traditional attitude towards marriage, suggesting that women who prioritize their careers and financial independence are more likely to delay or reconsider marriage. These findings underscore the complex interplay of social, individual, and cultural factors influencing unmarried women’s attitude towards marriage in contemporary Chinese society. Policymakers and social institutions are encouraged to consider these dynamics when developing strategies to address evolving marriage trends.